(untitled) (Global Journal of Medical Research, 1970)
In the climatic conditions of the Fergana Valley of Uzbekistan, 2478 people aged 18-70 engaged in farming were studied in a one-time epidemiological study. Questionnaire, clinical, biochemical, instrumental and special urological examination methods were used. The clinical symptoms of urolithiasis are determined to have a number of specific features, including risk factors and comorbidity. Severe urolithiasis and exacerbation of symptoms are observed in patients with a risk factor of 12.8 times, and in the presence of comorbidity - up to 45.7%.